Role of the Perceived Social Responsibility of the Company and the Psychological Mechanisms to Achieve the Employees' Creative Behavior (Case Study: Electro Kavir Company of Yazd) - Marziyeh Dehghanizadeh; Fatemeh Keshavarzi Hedesh (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of the current research is to investigate the role of the perceived social responsibility of the company and the psychological mechanisms to achieve the employees' creative behavior in Electro Kavir Company of Yazd. The method of this study is applicable based on the purpose, and descriptive-survey in terms of data collection. The statistical population of this study included all employees of Electro Kavir Company in Yazd (380), among which 191 people were selected through simple random sampling as the sample size. The data collection tool in this research was standard questionnaires, the validity of which was confirmed using the opinions of a number of experts in this field, and Cronbach's alpha coefficient and composite reliability were used to determine the reliability of the measurement tool, and the analysis method used in this research was structural equation modeling technique. The findings showed that the perceived corporate social responsibility has a significant relationship with creative behavior of employees, emotional commitment, compassion at workplace and internal motivation of employees. Also, the variables of emotional commitment, compassion at workplace and internal motivation of employees have a significant relationship with creative behavior of employees. The mediating role of emotional commitment, compassion at workplace and internal motivation of employees in the relationship between perceived corporate social responsibility and creative behavior of employees was also confirmed. Therefore, according to the results of the research, it was found that by using the theory of social identity, the employees' understanding of the social responsibility of the Electro Kavir Company of Yazd increased the emotional commitment and compassionate actions of the company's employees, and this increased the effects of the internal motivation of the employees, and thus, the creative behavior of the company's employees increases. Extended Abstract Introduction Today, in the dynamic business world, companies must promote creativity and innovation in order to remain competitive and stable in their industries, therefore both companies and employees are inclined to innovation and the personnel who, in order to achieve their goals, are aligned with the strategic goals of the organization are the most valuable employees, and their creativity is the basis of a company's success or failure and is considered as the most essential asset of a company; it strengthens the company's growth and increases its success and chances of survival and plays an important role in the company's performance (Audretsch, B. D., & Belitski, 2023; Fu et al., 2022: 1). And because employees are the main pillar of any organization, being creative and innovative of the organization depends on their creativity (Wang et al., 2019). Wang & Miao, (2015) showed in their research that creativity and innovation in organizational teams leads various processes of the organization to become more optimal, and influences the environment of the organization to implement creativity and innovation. Since creativity is important for organizational innovation and increases competitiveness, many researches have investigated individual and structural factors that may stimulate creative ideas in the workplace (Ganjaei & Hazrati, 2017:3). Therefore, as mentioned, the key to the success of many industries, including industries active in the electronics sector, is to provide creative products and services according to the different needs of customers, and since the creativity of employees creates competitive advantages for organizations, Electro Desert Yazd Company should also try to investigate the factors that increase the creative behavior of employees. Among the various results of scientists' research, the impact of employees' understanding of their company's social responsibility on employees' creative behavior has recently been the focus of researchers (Hur et al., 2018: 630). Therefore, in this research, the relationship between employees' understanding of the company's social responsibility and creative behavior of employees, as well as the basic mediation mechanisms of the three variables of emotional commitment, compassion in the work environment, and intrinsic motivation, which has not been addressed in any research so far, has been investigated and it tries to help the Empirical development in the literature. Therefore, this research in Yazd Electro Desert Company, which needs the creative behavior of employees to achieve a competitive advantage; tries to investigate whether the employees' understanding of the social responsibility of Electro Desert Company has increased the emotional commitment of the employees, and whether this increase in commitment has caused a compassionate behavior among the employees, and whether this has led to an increase in the internal motivation of the employees who want to behave creatively without external expectations. Theoretical Framework Creative behavior of employees Creativity is the use of mental ability to create a purposeful change in the social or economic power of the organization (Saleh & Brem, 2023). According to Anderson et al., (2014), creativity and novelty are the results of new ideas and improved tasks in the form of products and work processes, and employees of an organization should behave creatively in performing their role and extra-role tasks. Corporate social responsibility Corporate social responsibility is a way of management that organizations should perform activities that have a positive effect on society. In fact, Stuart and Salmon's attitude was based on the fact that they wanted to eliminate the negative effects of the organization on society and tried to change the attitude and behavior of consumers (Stuart, 1998). Fleming also pointed out that social responsibility is the responsibility of companies that companies should not have a negative impact on the social life in which they work. These duties include not polluting the environment; non-discrimination in hiring people; not engaging in unethical activities; Production of qualitative products and positive participation in the lives of people in society (Fleming, 2012). Emotional commitment Emotional commitment refers to a person's emotional attachment to the organization and its goals. In other words, emotional commitment is conceptualized as employees' emotional feeling of belonging to the organization, identification with it, and involvement and participation in the organization. People with strong emotional commitment did not leave the organization; because they like to be a member of the organization (Ahangary et al., 2016; Dziuron & Halaszovich, 2023). Compassion in the workplace Compassion in the workplace refers to a collective aspect, where people notice suffering among one or more colleagues, empathize with them, understand the cause of suffering, and finally take collective action to reduce suffering (Chatterjee et al., 2021: 2). Compassion can be described as a person's willingness to devote time and effort to the well-being of others (Chen & Liu, 2023). Intrinsic motivation Doing an activity in itself is called intrinsic motivation rather than the desire for external reward (Feiz et al., 2020: 149). Intrinsic motivation is defined as an individual characteristic in which a person has an internal motivation to achieve something for their own internal satisfaction, not for external benefits (Chen & Liu, 2023). Research Methodology Considering that, the present research sought to investigate the role of the perceived social responsibility of the company and psychological mechanisms (emotional commitment, compassion in the work environment and internal motivation) to achieve the creative behavior of employees in Electro Desert Company in Yazd city, it is practical in terms of the objective, and, descriptive-survey type in terms of the method of data collection. The statistical population of this research includes all the employees of Electro Desert Company in Yazd city, numbering 380 people, from which a sample size of 191 people was determined by using Cochran's formula. Of course, in this research, the method of obtaining the number of sample sizes in SmartPLS3 software, which uses the partial least squares technique, was also investigated; its method is such that the number ten is multiplied by the number of indicators of the measurement model, which has the most indicators among the measurement models of the main research model (Davari & Rezazadeh, 2014: 75). It should be mentioned that in the present study, the highest indicator is related to the variable of emotional commitment, which has eight items and ten times it, the number becomes 80, so the sample size is sufficient for the research model. The tool for collecting information in this research was standard questionnaires; and the questionnaire of perceived social responsibility of the company from the study of Su & Swanson, (2019); Questionnaire of creative behavior of employees from the study of Hur et al., (2018); Emotional commitment questionnaire from the study of Meyer & Allen, (1997); Compassion in the workplace questionnaire from the study of Cameron et al., (2004); and internal motivation questionnaire from the study of Hur et al., (2018) were used, the content validity of which was checked and confirmed by management professors and experts. Both divergent and convergent validity index and factor loadings were also used to check the validity; and the reliability of the research instrument was calculated and confirmed by two methods, Cronbach's alpha coefficient and composite reliability. Research Findings The analysis method used in this research to test the research hypotheses was the structural equation modeling technique, and the research findings showed that all the values ​​obtained for the fit indices are acceptable. The findings regarding the hypothesis test showed that the perceived social responsibility of the company has a significant relationship with Creative behavior of employees, emotional commitment, compassion in the work environment, and internal motivation of employees. Also, the variables of emotional commitment, compassion in the work environment, and internal motivation of employees have a significant relationship with the creative behavior of employees, and finally the mediating role of emotional commitment, compassion in the work environment, and internal motivation of employees in the relationship between the perceived social responsibility of the company and the creative behavior of employees was confirmed.. Conclusion The present study was conducted with the aim of investigating the role of the perceived social responsibility of the company and psychological mechanisms (emotional commitment, compassion in the work environment, and intrinsic motivation) to achieve the creative behavior of employees in the Electro Desert Company of Yazd. This research tried to investigate, according to the theory of social identity and self-determination, how the macro concept of social responsibility of Electro Desert Company can directly and indirectly affect the micro concepts, such as compassion, commitment, motivation and creative behavior of employees. Therefore, according to the results of the research, it was found that by using the theory of social identity, the employees' understanding of the social responsibility of the Yazd Electro Desert Company increased the emotional commitment and compassionate actions of the company's employees, and considering that a company with social responsibility, pays attention not only to It internal stakeholders, but to external stakeholders such as customers, society and even its environment, and works for their interests; therefore, such a company that prefers the interests of the whole over personal interests, causes employees to be encouraged, do not consider only their personal benefit, and find their job attractive and meaningful to help the society; and this strengthens their internal motivation, and they don't need external rewards to be motivated; thus, the ethical participation and social responsibility of Yazd Electro Desert Company instills a sense of respect and trust among the employees, and by using the self-determination theory, it in turn has a positive effect on the internal motivation of the employees, and thus, the creative behavior of the employees of this company increases.